2019
DOI: 10.1096/fj.201900073r
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mitophagy in mt‐Keima Drosophila revealed an essential role of the PINK1‐Parkin pathway in mitophagy induction in vivo

Abstract: Mitophagy has been implicated in mitochondrial quality control and in various human diseases. However, the study of in vivo mitophagy remains limited. We previously explored in vivo mitophagy using a transgenic mouse expressing the mitochondria‐targeted fluorescent protein Keima (mt‐Keima). Here, we generated mt‐Keima Drosophila to extend our efforts to study mitophagy in vivo. A series of experiments confirmed that mitophagy can be faithfully and quantitatively measured in mt‐Keima Drosophila. We also showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 50 publications
3
78
0
Order By: Relevance
“…Jan (University of California, San Francisco, CA). The UAS-mt-Keima line was generated previously [19]. The UAS-PINK1 and PINK1 RNAi lines were generated previously [16].…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…Jan (University of California, San Francisco, CA). The UAS-mt-Keima line was generated previously [19]. The UAS-PINK1 and PINK1 RNAi lines were generated previously [16].…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…Recent Drosophila studies also support the notion that PINK1-Parkin signalling is dispensable for basal mitophagy, but may also play a role in stress-induced mitophagy [126,127]. Independent of mitophagy, other studies have delineated the mechanics of how matrix-localised mtDNA can activate cGAS-STING signalling [163], and have also linked cGAS-STING signalling to macroautophagy [164].…”
Section: Pink1/parkin In Vivo: If Not Mitophagy Then What?mentioning
confidence: 80%
“…Additionally, microglia and cerebral vasculature also had noticeably high levels of mitochondrial turnover [122]. Recent data utilising these reporters also demonstrated the conservation of basal mitophagy from mammals to flies [126,127].…”
Section: Mitophagy In Healthy Tissuesmentioning
confidence: 99%
“…However, the effects on mitochondrial protein half-lives were only weakly correlated between the two mutants, suggesting either that mitophagy may be influenced by Parkinindependent regulatory pathways or that Parkin may regulate mitochondrial protein turnover through autophagyindependent mechanisms [107]. Moreover, three of the previously mentioned studies found that PINK1 and Parkin knockouts had no effect on basal mitophagy in mouse and Drosophila [103][104][105], whereas one study found that PINK1 or Parkin deficiency in Drosophila abrogated an age-dependent increase in basal mitophagy [106]. Furthermore, if driving mitophagy is a primary role of endogenous Parkin/PINK1, then one might expect that loss of either gene would lead to accumulation of mitochondria.…”
Section: Pink1/parkin Regulate Tiers Of Mitochondrial Quality Controlmentioning
confidence: 99%
“…A few recent studies using mitochondria-targeted pHsensitive fluorescent indicators suggest that low levels of basal mitophagy occur throughout both wild-type mouse and Drosophila brains, including in DA neurons [101][102][103][104][105][106]. The rate of basal mitophagy appears to increase with the metabolic demands of the tissue and in response to stressors such as hypoxia and mtDNA mutagenic stress [102,104,106].…”
Section: Pink1/parkin Regulate Tiers Of Mitochondrial Quality Controlmentioning
confidence: 99%